[East Timor in transition, 2000-2002 collection of brochures and booklets]. - United Nations. Transitional Administration in East Timor ([Dili : UNTAET, 2002)
Collection of booklets, flyers, brochures and cartoons illustrating slogans used during the period of transition in East Timor.
Title supplied by cataloguer.
Tetum or English.
Digital content preserved
Keywords: Timor-Leste -- History -- Autonomy and independence movements; Timor-Leste -- Politics and government